2014
DOI: 10.1016/j.eswa.2013.05.067
|View full text |Cite
|
Sign up to set email alerts
|

eXiTCDSS: A framework for a workflow-based CBR for interventional Clinical Decision Support Systems and its application to TAVI

Abstract: Clinical Decision Support Systems (CDSSs) should form an important part of the field of clinical knowledge management technologies through their capacity to support the clinical process and use of knowledge, including knowledge maintenance and continuous learning, from diagnosis and investigation through surgery, treatment and long-term care. The work presented shows a workflow-based CDSS designed to give case-specific assessment to clinicians during complex surgery or Minimally Invasive Surgerys (MISs). Follo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 33 publications
0
16
0
Order By: Relevance
“…As is known to all, the case-based reasoning (CBR) technique is good at solving problems by retrieving and reusing information and knowledge of the similar historical cases (Aamodt & Plaza, 1994;Abelson & Schank, 1977;Hansen, Meservy, & Wood, 1994). Over the decades, CBR was widely applied in various areas such as medicine (El-Fakdi, Gamero, Meléndez, Auffret, & Haigron, 2014;Guessoum, Laskri, & Lieber, 2014;Ting, Wang, Kwok, Tsang, & Lee, 2010;Zhuang, Churilov, Burstein, & Sikaris, 2009), manufacturing industry (Kuo, 2010;Wu, Lo, & Hsu, 2008) and business (Carmona, Barbancho, Larios, & León, 2013;Li, Adeli, Sun, & Han, 2011), etc. It can been found that there are some studies on risk management based on CBR (Aarts, 1998;Bajo, Borrajo, De Paz, Corchado, & Pellicer, 2012;Chang, Ma, Song, & Gao, 2010;Dingwei & Xinping, 2011;Goh & Chua, 2009;Jung, Han, & Suh, 1999;Kumar & Viswanadham, 2007;Li, Yu, Zhou, & Cai, 2013;Lu, Li, & Xiao, 2013;Yao, Chen, & Yang, 2014).…”
Section: Introductionmentioning
confidence: 98%
“…As is known to all, the case-based reasoning (CBR) technique is good at solving problems by retrieving and reusing information and knowledge of the similar historical cases (Aamodt & Plaza, 1994;Abelson & Schank, 1977;Hansen, Meservy, & Wood, 1994). Over the decades, CBR was widely applied in various areas such as medicine (El-Fakdi, Gamero, Meléndez, Auffret, & Haigron, 2014;Guessoum, Laskri, & Lieber, 2014;Ting, Wang, Kwok, Tsang, & Lee, 2010;Zhuang, Churilov, Burstein, & Sikaris, 2009), manufacturing industry (Kuo, 2010;Wu, Lo, & Hsu, 2008) and business (Carmona, Barbancho, Larios, & León, 2013;Li, Adeli, Sun, & Han, 2011), etc. It can been found that there are some studies on risk management based on CBR (Aarts, 1998;Bajo, Borrajo, De Paz, Corchado, & Pellicer, 2012;Chang, Ma, Song, & Gao, 2010;Dingwei & Xinping, 2011;Goh & Chua, 2009;Jung, Han, & Suh, 1999;Kumar & Viswanadham, 2007;Li, Yu, Zhou, & Cai, 2013;Lu, Li, & Xiao, 2013;Yao, Chen, & Yang, 2014).…”
Section: Introductionmentioning
confidence: 98%
“…In our study the CBR is aimed at the management of valvular heart disease and especially at the planning of Transcatheter Aortic Valve Implantation (TAVI). The feasibility of designing CBR for TAVI has been previously reported in El-Fakdi et al [4]. Their work concentrated on the overall framework and did not focus on investigating similarity functions.…”
Section: Introductionmentioning
confidence: 99%
“…Dong and Srinivasan (2013) presented an agent-enabled service-oriented DSS for managerial decision making. El-Fakdi et al (2013) presented an in-debt discussion on the implementation of DSS in clinical medications.…”
Section: Introductionmentioning
confidence: 99%